Color blocked - Sorenson, Ashley N.; Miles, David (David W.) (2017)
"The color is blocked! Readers must rub, turn, and tap the pages to straighten out pipes, unplug corks, and keep the color flowing. But watch out the color might run faster than you can keep up! Along the way, readers will learn primary colors, how mixing colors can make secondary colors, and why you should never, ever, put too much trust in a narrator"--Back cover.
Keywords: Colors -- Juvenile fiction; Play -- Juvenile fiction; JUVENILE FICTION / Concepts / Colors; Colors; Play; Fiction; Juvenile works